Strategi Pengembangan Budidaya Jamur Tiram Di Kabupaten Magetan - Widita Nareswari; Abu Talkah; Ahsin Daroini (Universitas Merdeka Madiun, 2019)
Magetan Regency which is located in the western end of East Java Province geographically has the potential in agriculture in the development of horticultural commodities namely oyster mushrooms. Oyster mushroom cultivation in Magetan Regency is relatively new with supporting factors such as affordable raw materials; cultivation techniques that are easy to learn; and humidity factors that support but have weaknesses, one of which is capital; farmer's motivation and tenacity; and the absence of technology application. Based on these conditions, this study aims to: (1) Identify and analyze internal and external factors that influence the development of oyster mushroom agribusiness in Magetan Regency (2) Formulate alternatives and recommend priorities for the development of oyster mushroom in the Regency Magetan. This research uses SWOT analysis and Process Hierarchy Analysis (AHP). The results showed the influential factors that obtained the highest score factors were organic crops, limited capital, motivation and persistence of farmers, public awareness of healthy food, weather and pests. Whereas the alternative that has the highest three priority values is to increase the number of baglogs along with the quality of the baglog quality of mushroom seeds, the application of appropriate management and human resources, and expand the reach of market share and the use of technology in marketing.